Soft Skills and Their Wage Returns: Overview of Empirical Literature - Jiří Balcar (Review of Economic Perspectives, 2014)
Psychological traits, attitudes and soft skills represent factors whose effect on an individual's wages has begun to be examined recently. Today, there is an extensive empirical body on wage returns to the first two factors, but still a relatively small one on wage returns to soft skills, such as communication, cooperation, leadership etc. The aim of this paper is to provide an overview of empirical literature on wage returns to soft skills. It suggests that soft skills are connected with significant wage returns and contribute to closing the gender wage gap. The end of the paper focuses on a discussion on methodological approaches to measurement of soft skills and relevancy of their approximation by job characteristics (incl. suggestion of using tools of competency modelling for this purpose).
Keywords: 330